Whole transcriptome analysis of human erythropoietic cells during ontogenesis suggests a role of VEGFA gene as modulator of fetal hemoglobin and pharmacogenomic biomarker of treatment response to hydroxyurea in β-type hemoglobinopathy patients - Chondrou, Vasiliki (Hum Genomics, 2017)
BACKGROUND: Human erythropoiesis is characterized by distinct gene expression profiles at various developmental stages. Previous studies suggest that fetal-to-adult hemoglobin switch is regulated by a complex mechanism, in which many key players still remain unknown. Here, we report our findings from whole transcriptome analysis of erythroid cells, isolated from erythroid tissues at various developmental stages in an effort to identify distinct molecular signatures of each erythroid tissue. RESULTS: From our in-depth data analysis, pathway analysis, and text mining, we opted to focus on the VEGFA gene, given its gene expression characteristics. Selected VEGFA genomic variants, identified through linkage disequilibrium analysis, were explored further for their association with elevated fetal hemoglobin levels in β-type hemoglobinopathy patients. Our downstream analysis of non-transfusion-dependent β-thalassemia patients, β-thalassemia major patients, compound heterozygous sickle cell disease/β-thalassemia patients receiving hydroxyurea as fetal hemoglobin augmentation treatment, and non-thalassemic individuals indicated that VEGFA genomic variants were associated with disease severity in β-thalassemia patients and hydroxyurea treatment efficacy in SCD/β-thalassemia compound heterozygous patients. CONCLUSIONS: Our findings suggest that VEGFA may act as a modifier gene of human globin gene expression and, at the same time, serve as a genomic biomarker in β-type hemoglobinopathy disease severity and hydroxyurea treatment efficacy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40246-017-0120-8) contains supplementary material, which is available to authorized users.